*3(*5+*15) = *3*5 + *3*15
since 15 = 3x5:
=*3*5 + *3*3*5 = *3*5 + 3*5 = (3+*3)*5
2006-12-10 09:56:43
·
answer #1
·
answered by Emily 3
·
0⤊
0⤋
*3(*5+*15) = *15 (1 + *3)
2006-12-10 18:10:39
·
answer #2
·
answered by James Chan 4
·
0⤊
0⤋
*3(*5+*15) =
*15 +*45=
*15 + (*9)(*5) =
*15 + 3*5
2006-12-10 17:59:04
·
answer #3
·
answered by ironduke8159 7
·
0⤊
0⤋
square root of 3 times (square root of 5 plus the square root of 15)
just do *(3x5) plus *(3x15) which is *15+*45 and simplify from there so it's *15 plus 3*15 which is 4*15. mostly just distribute and you'll be fine.
2006-12-10 17:56:06
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
ok start in the brackets
square root 5 is 2.23 and add square root 15 which is 3.87
giving you 6.11
ok?
then u need to multiply by the sum out side brackets
so square root of 3 is 1.73
so answer is 1.73 x 6.11 which is 10.58
that ok ?
2006-12-10 17:58:13
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
distribute:
(*3 times * 5 + *3 times * 15) simplify:
*15+*45 simplify:
*15+3*5 =
about : 3.83+6.71 = 10.58
2006-12-10 17:56:31
·
answer #6
·
answered by luna y 1
·
0⤊
0⤋
*3(*5 + *15)
*15 + *45.
That's as far as it can be simplified without going to long decimals.
2006-12-10 17:54:04
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
i think this is a surd problem, not sure if this is right but:
*3(*5+*15)
=*15+*45
=*15 + *15x*15 + 3*15
=4*15
2006-12-10 17:57:49
·
answer #8
·
answered by Ryujin 3
·
0⤊
1⤋
*15 + *45 ~= 10.6
2006-12-10 17:53:39
·
answer #9
·
answered by jacinablackbox 4
·
0⤊
0⤋
~10.58
2006-12-10 17:56:40
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋